Pengaruh Struktur Permodalan, Dewan Komisaris Independen, Dan Pengungkapan Kinerja ESG Terhadap Nilai Perusahaan Di Sektor Makanan Dan Minuman Di Bursa Efek Indonesia - Gede Aditya Putra Utaman; Ketut Tanti Kustina (Fakultas Ekonomi Universitas Warmadewa, 2026)
This study aims to analyze the influence of capital structure, independent board of commissioners, and environmental, social, and governance performance disclosure on the value of food and beverage companies listed on the Indonesia Stock Exchange during the 2022-2023 period. Capital structure is measured by the Debt to Equity Ratio (DER). The board of independent commissioners is measured by the number of commissioners divided by the independent commissioners. Disclosure of environmental, social, and governance performance measured by ESG scores. The company's value is proxied using Price to Book Value (PBV). This study uses a quantitative approach with multiple linear regression method to test the relationship between variables. The data used are secondary data obtained from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange and ESG disclosure reports for food and beverage listed on the BGK Foundation. Samples were determined by purposive sampling method. The results of the analysis show that the capital structure has no effect on the value of the company. The independent board of commissioners and the disclosure of ESG performance show a positive and significant influence on the company's value. These findings indicate that the number of independent commissioners and ESG performance disclosures are the main factors that investors consider in assessing a company's performance, while capital structure has a more limited role in determining the value of the company.